Faktor-Faktor Penentu Pola Pembelajaran Petani dalam Pengembangan Padi Sawah Organik di Kabupaten Kolaka Timur - Arimbawa, Putu; Batoa, Hartina; Afa, Laode (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This study aimed to analyze the determinants of farmers’ learning patterns in developing organic lowland rice. This research is a survey research with the research location in Lambandia District, East Kolaka Regency, Southeast Sulawesi Province. The was chosen because some farmers have applied organic lowland rice cultivation technology. The research period was for three months, from July to September 2021. The number of samples was 62 farmers by the census. Research variables were farmers’ characteristics, access to information media, support of supporting factors, and farmer learning patterns. collecting data with structured interviews using a questionnaire. Data analysis used descriptive analysis and SEM-PLS analysis. The results showed that the farmer’s learning pattern was through imitation of innovation with the support of the availability of creation and assistance. Farmer characteristics, supporting factors, and farmer access to information affect farmer learning patterns.